Characteristics of Libido and Testosterone Concentration of Polled and Horned Bali Bulls after GnRH Injection - Hasbi Hasbi; Herry Sonjaya; Sudirman Baco; Reski Amalia; Sri Gustina (Jurnal Ilmu Ternak dan Veteriner, 2021)
Bali cattle are one of the original Indonesian germplasm, which in its development were found to be hornless or polled. Polled are Balinese cattle whose horns do not grow naturally, but have the same characteristics as those with horns. However, there are indications that polled have a lower libido. The purpose of this study was to determine the characteristics of libido and testosterone concentration after gonadotrophin releasing hormone (GnRH) injection. In this study each of 7 male polled and horned Bali cattle aged 3.5-6 years were used. Libido characteristics were observed by recording the first time the male fondled the teaser until ejaculation, while the testosterone concentration was measured using blood plasma taken on day 0 or before injection, day 7th, and day 14th after GnRH injection. Testosterone analysis used enzyme linked immunosorbent assay (ELISA) method. The results showed that the libido of polled was not different (P>0.05) compared to that of the horned on the 0, 7th and 14th days after GnRH injection. However, in polled on the 7th day after GnRH injection, it was significantly lower than on day 0 and 14, but on day 0 it was not different with day 14. Testosterone concentration on day 7 after injection of GnRH was not different (P>0.05) compared to day 0 both in polled and horned bulls, but on day 14 after injection was significantly higher (P<0.05) in horned than polled. In conclusion, polled and horned Bali bulls had high libido with a score of +1, but on the 7th day after GnRH injection, polled had lower libido than horns. The testosterone concentrations of polled and horned on day 7 after GnRH injection were not different compared to day 0, while the 14th day was higher in horned bull.